Aromatic polycarbonate resin composition and molded article made thereof

JP7644644B2Active Publication Date: 2025-03-12TEIJIN LTD
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2021057015
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-03-30
Publication Date
2025-03-12
Estimated Expiration
2041-03-30

AI Technical Summary

Benefits of technology

【0019】 本発明のポリカーボネート樹脂組成物は、離型性および成形耐熱性に優れ、微量揮発ガス成分が高度に低減された芳香族ポリカーボネート樹脂組成物であり、OA機器分野、電気電子機器分野などの各種工業用途に有用であり、その奏する産業上の効果は格別である。例えば、電子部品、電子基板、磁気ディスク、集積回路チップへと加工されるウエハなどの半導体ウエハ、マスクガラス等の精密基板、その他精密電子材料など覆う外装成形品や周辺の成形部材、前述の各種電子材料を収納し、輸送、搬送、保管するための容器としての成形品や容器を構成する成形部材として有用である。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007644644000001
    Figure 0007644644000001
  • Figure 0007644644000002
    Figure 0007644644000002
  • Figure 0007644644000003
    Figure 0007644644000003
Patent Text Reader

Abstract

To provide an aromatic polycarbonate resin composition which has excellent releasability and molding heat resistance and in which a trace volatile gas component is highly reduced.SOLUTION: Provided is an aromatic polycarbonate resin composition prepared by adding, to 100 pts.wt. of (A) an aromatic polycarbonate resin (Component A), 0.01 to 0.12 pt.wt. of an aliphatic ester compound (Component B) constituted by a polyhydric alcohol and a higher fatty acid. A total of additives including the Component B and additives other than the Component B is 0.01 to 0.15 pt.wt. and the Component B has i) an acid value of 5 or less and ii) a 5% weight loss temperature in TGA (thermogravimetric analysis) is 300°C or higher.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to an aromatic polycarbonate resin composition which is excellent in mold releasability and molding heat resistance and has a highly reduced amount of volatile gas components by blending a required amount of a specific aliphatic ester compound. More specifically, the present invention relates to an aromatic polycarbonate resin composition which can be suitably used as a material for containers and covers used for storing or transporting various precision electronic materials such as wafers processed into magnetic disks or integrated circuit chips, and a molded article made of the same. [Background technology]

[0002] In resin containers for storing, transporting, carrying, and storing electronic components, electronic substrates, magnetic disks, semiconductor wafers, precision substrates such as mask glasses, and other precision electronic materials, there has been a demand for reducing the amount of impurities that cause trace amounts of volatile gases in the molding materials (thermoplastic resin compositions).To meet this demand, Patent Document 1 proposes a polycarbonate resin that has fewer impurity chlorine atoms and impurity metal atoms and is more transparent and impact-resistant than other resins.

[0003] In recent years, as the diameter of semiconductor wafers increases, the size of thin plate storage and transport containers has also increased. However, from the viewpoint of storage space, logistics costs, and raw material cost reduction, it is preferable to avoid unnecessary size, and the draft angle of the container is designed to be as small as possible. The larger the molded product is, and the smaller the draft angle, the greater the demolding load when the molded product is demolded. On the other hand, molded product structures have become more complex and precise in order to improve functionality, and some parts with small draft angles are unavoidable. For these reasons, there has been a trend in recent years to require material-based demolding properties, and a material suitable for this has been proposed in Patent Document 2. The material shown in Patent Document 2 is an aromatic polycarbonate resin composition for thin plate storage and transport containers that can reduce surface contamination of thin plates such as semiconductor wafers and magnetic disks, which are sensitive to surface contamination, and has excellent demolding properties during molding and excellent molding heat resistance.

[0004] Furthermore, with the advancement of miniaturization of semiconductor components and narrower pitches of wiring, there is a strong demand for molding materials used in containers for semiconductor wafers (precision substrates) to reduce trace amounts of volatile matter detected in the materials in order to prevent contamination of the wafers to a high degree. In order to meet this demand, it is necessary to further reduce trace amounts of volatile matter while maintaining a certain degree of releasability in the technology of Patent Document 2, and the selection of the aliphatic ester used as the release agent and its blending amount are important.

[0005] On the other hand, Patent Documents 3 and 4 are interesting in that they refer to the types of aliphatic esters to be blended into the polycarbonate resin and their characteristic values, but the blended amount of the aliphatic esters exceeds 0.2% by weight, and is not intended to significantly reduce trace volatile content. Patent Document 5 also limits the amount of aliphatic esters to be blended to the minimum necessary, but the aliphatic ester compounds limited thereto are the same as those shown in Patent Document 2, and are not effective in further reducing trace volatile content, and the maximum total blended amount of additives including phosphorus-based antioxidants exceeds 1% by weight. [Prior art documents] [Patent documents]

[0006] [Patent Document 1] Patent No. 3995346 [Patent Document 2] Patent No. 5749335 [Patent Document 3] Patent No. 5893856 [Patent Document 4] Patent No. 5806008 [Patent Document 5] Patent No. 6575979 Summary of the Invention [Problem to be solved by the invention]

[0007] An object of the present invention is to provide an aromatic polycarbonate resin composition which is excellent in mold releasability and molding heat resistance and in which the amount of volatile gas components emitted is significantly reduced. [Means for solving the problem]

[0008] As a result of intensive research, the present inventors have found that the above object can be achieved by blending a small amount of a specific aliphatic ester compound, the characteristic values ​​of which are regulated, in an aromatic polycarbonate resin composition, and by blending limited amounts of additives other than the aliphatic ester compound, and have arrived at the present invention.

[0009] That is, according to the present invention, the following configurations (1) to (9) are provided.

[0010] (1) An aromatic polycarbonate resin composition comprising 100 parts by weight of (A) an aromatic polycarbonate resin (component A) and 0.01 to 0.12 parts by weight of (B) an aliphatic ester compound (component B) composed of a polyhydric alcohol and a higher fatty acid, wherein the total amount of the additives blended, including component B and additives other than component B, is 0.01 to 0.15 parts by weight, and the component B is (i) an acid value of 5 or less; (ii) The 5% weight loss temperature in TGA (thermogravimetric analysis) is 300°C or higher; 1. An aromatic polycarbonate resin composition comprising:

[0011] (2) The aromatic polycarbonate resin composition according to item 1 above, wherein the viscosity average molecular weight of component A is in the range of 18,000 to 23,000.

[0012] (3) The aromatic polycarbonate resin composition according to item 1 or 2 above, in which the component B is blended in an amount of 0.015 to 0.07 parts by weight, and the total amount of blended additives including the component B and additives other than the component B is 0.015 to 0.10 parts by weight.

[0013] (4) The aromatic polycarbonate resin composition according to any one of items 1 to 3 above, wherein the 5% weight loss temperature of component B as determined by thermogravimetric analysis (TGA) is 330° C. or higher.

[0014] (5) The aromatic polycarbonate resin composition according to any one of items 1 to 4 above, wherein Component B is an aliphatic ester compound having a full ester of pentaerythritol as a main component.

[0015] (6) The aromatic polycarbonate resin composition according to any one of items 1 to 5 above, wherein the aromatic polycarbonate resin composition has a chlorine atom content of 5 ppm or less.

[0016] (7) A molded article obtained by molding the aromatic polycarbonate resin composition according to any one of items 1 to 6 above.

[0017] (8) The molded product according to the preceding paragraph 7, which is a container for storing and transporting thin plates.

[0018] (9) The molded product according to the preceding paragraph 8, wherein the thin plate storage and transport container is a storage and transport container for semiconductor wafers. Effect of the Invention

[0019] The polycarbonate resin composition of the present invention is an aromatic polycarbonate resin composition with excellent mold releasability and molding heat resistance, and with a highly reduced amount of volatile gas components, and is useful for various industrial applications such as the OA equipment field and the electric and electronic equipment field, and has exceptional industrial effects. For example, it is useful as an exterior molded product or peripheral molded part that covers electronic parts, electronic substrates, magnetic disks, semiconductor wafers such as wafers processed into integrated circuit chips, precision substrates such as mask glasses, and other precision electronic materials, and as a molded product or molded part that constitutes a container for storing, transporting, conveying, and storing the various electronic materials described above. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0020] The present invention will be described in detail below.

[0021] <Component A: Aromatic polycarbonate resin> The aromatic polycarbonate resin used in the present invention is obtained, for example, by reacting a dihydric phenol with a carbonate precursor by a solution method or a melt method. Representative examples of the dihydric phenol used herein include 2,2-bis(4-hydroxyphenyl)propane (commonly known as bisphenol A), bis(4-hydroxyphenyl)methane, 1,1-bis(4-hydroxyphenyl)ethane, 1,1-bis(4-hydroxyphenyl)cyclohexane, 2,2-bis(4-hydroxy-3,5-dimethylphenyl)propane, 2,2-bis(4-hydroxy-3,5-dibromophenyl)propane, 2,2-bis(4-hydroxy-3-methylphenyl)propane, bis(4-hydroxyphenyl)ether, 4,4-dihydroxydiphenyl, bis(4-hydroxyphenyl)sulfide, bis(4-hydroxyphenyl)sulfone, and the like. A preferred dihydric phenol is bis(4-hydroxyphenyl)alkane, and among them, bisphenol A is particularly preferred.

[0022] As the carbonate precursor, carbonyl halide, carbonate ester, haloformate, etc. are used, and specifically, phosgene, diphenyl carbonate, dihaloformate of dihydric phenol, etc. are mentioned.

[0023] When producing an aromatic polycarbonate resin by reacting the above dihydric phenol with a carbonate precursor by a solution method or a melt method, the dihydric phenol can be used alone or in combination of two or more, and a catalyst, a terminal stopper, an antioxidant for the dihydric phenol, etc. may be used as necessary. Further, the aromatic polycarbonate resin may be a branched polycarbonate resin copolymerized with a polyfunctional aromatic compound having three or more functional groups, or a polyester carbonate resin copolymerized with an aromatic or aliphatic, preferably aromatic or aliphatic dicarboxylic acid having 8 or more carbon atoms, or a mixture of two or more aromatic polycarbonate resins.

[0024] In the present invention, the solution method is particularly preferably used, and the reaction by the solution method is usually a reaction between a dihydric phenol and phosgene, which is carried out in the presence of an acid binder and an organic solvent. As the acid binder, for example, an alkali metal hydroxide such as sodium hydroxide or potassium hydroxide, or an amine compound such as pyridine, is used. As the organic solvent, for example, a halogenated hydrocarbon such as methylene chloride or chlorobenzene is used. In addition, a catalyst such as a tertiary amine or a quaternary ammonium salt can be used to promote the reaction. In this case, the reaction temperature is usually 0 to 40°C, and the reaction time is about several minutes to 5 hours.

[0025] In addition, in such a polymerization reaction, a monofunctional phenol can be used as a terminal terminator. Monofunctional phenols are generally used as terminal terminators for molecular weight control, and the obtained polycarbonate resin has excellent thermal stability compared to those not having the terminals blocked by groups based on monofunctional phenols. Such monofunctional phenols are generally phenol or lower alkyl-substituted phenols, and can be represented by the following formula (I).

[0026] [ka]

[0027] (In the formula, R represents a hydrogen atom or an alkyl group having 1 to 9 carbon atoms, preferably 1 to 8 carbon atoms, and m represents an integer of 0 to 5, preferably 0 to 3.)

[0028] Specific examples of the monofunctional phenols include phenol, p-tert-butylphenol, p-cumylphenol, and isooctylphenol.

[0029] The reaction by the melting method is usually an ester exchange reaction between a dihydric phenol and diphenyl carbonate, in which the dihydric phenol and diphenyl carbonate are mixed in the presence of an inert gas, and the reaction is usually carried out under reduced pressure at 120 to 350°C, preferably using a polymerization catalyst such as an alkaline (earth) metal compound to accelerate the polymerization rate. The degree of reduced pressure is changed stepwise, and finally reduced to 1 mmHg or less to remove the generated phenols from the system. The reaction time is usually about 1 to 4 hours.

[0030] The molecular weight of the aromatic polycarbonate resin used in the present invention is preferably in the range of 18,000 to 23,000 in terms of viscosity average molecular weight, more preferably 18,100 to 22,500, even more preferably 18,200 to 22,000, particularly preferably 18,300 to 21,000, and most preferably 18,400 to 20,000. Aromatic polycarbonate resins having such a viscosity average molecular weight have a certain mechanical strength and good flowability during molding, which is preferable. If the molecular weight is low, the molded product will not have enough strength, making it difficult to obtain a practical material. If the molecular weight is high, problems such as poor molding flowability are likely to occur, and further, problems such as phenolic compounds and chlorine-based organic solvents that cause trace volatile content detection are likely to remain in the resin are likely to occur. If the extrusion temperature is increased to solve this problem, the chlorine-based organic solvents will be reduced, but the decomposition of the resin may progress and the amount of phenolic compounds may increase.

[0031] The viscosity average molecular weight (M) in the present invention is the specific viscosity (η SP ) into the following formula: η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7

[0032] Regarding the measurement of the specific viscosity, for example, it can be carried out as follows. First, the polycarbonate resin is dissolved in methylene chloride at 20 to 30 times its weight. After collecting the soluble component by filtration through Celite, the solution is removed and dried thoroughly to obtain the solid of the methylene chloride-soluble component. The specific viscosity at 20 °C is determined from a solution prepared by dissolving 0.7 g of such a solid in 100 ml of methylene chloride using an Ostwald viscometer.

[0033] <Component B: Aliphatic ester compound> The aromatic polycarbonate resin composition of the present invention is characterized in that 0.01 to 0.12 parts by weight of an aliphatic ester compound (Component B) composed of a polyhydric alcohol and a higher fatty acid is blended with respect to 100 parts by weight of the aromatic polycarbonate resin. It is characterized by being formulated.

[0034] The aliphatic ester compound composed of a polyhydric alcohol and a higher fatty acid is preferably 0.01 to 0.10 parts by weight, more preferably 0.015 to 0.07 parts by weight, and still more preferably 0.02 to 0.05 parts by weight with respect to 100 parts by weight of the aromatic polycarbonate resin. If the blending amount of the aliphatic ester compound is less than the above range, the mold release property during molding deteriorates and the molding processability deteriorates, which is not preferable. If the blending amount of the aliphatic ester compound exceeds the above range, a slight decrease in heat resistance during molding occurs, and the aromatic polycarbonate resin is slightly more likely to decompose, increasing the amount of phenolic compounds as trace volatile components, or increasing the trace volatile components detected from the aromatic polycarbonate resin composition due to the volatilization and decomposition of the aliphatic ester compound itself, which is not preferable.

[0035] In the aliphatic ester compound used in the present invention, it is important to select the type of aliphatic ester compound so as to satisfy (i) an acid value of 5 or less and (ii) a 5% weight loss temperature of TGA (thermogravimetric analysis) of 300 °C or higher.

[0036] In addition, when two or more types of aliphatic ester compounds are blended, the "acid value" and "5% weight loss temperature in TGA (thermogravimetric analysis)" of component B shall be the weighted average value of each value of each aliphatic ester compound.

[0037] When the acid value of an aliphatic ester compound is greater than 5, or when the 5% weight loss temperature in TGA (thermogravimetric analysis) is less than 300°C, the contribution of the aliphatic ester compound itself to the aromatic polycarbonate increases, causing subtle decomposition of the aromatic polycarbonate resin and increasing the amount of trace volatile components that can be detected, or increasing the amount of trace volatile components that can be detected due to trace volatilization or trace decomposition of the aliphatic ester compound itself.

[0038] The acid value of the aliphatic ester compound is preferably 4.5 or less, more preferably 4 or less, and even more preferably 3.5 or less. The 5% weight loss temperature of the aliphatic ester compound by TGA (thermogravimetric analysis) is preferably 330°C or more, more preferably 350°C or more, and even more preferably 370°C or more.

[0039] The polyhydric alcohol constituting the aliphatic ester compound preferably has a carbon number of 3 to 32. Specific examples of such polyhydric alcohols include glycerin, diglycerin, polyglycerin (e.g., decaglycerin, etc.), pentaerythritol, dipentaerythritol, diethylene glycol, and propylene glycol.

[0040] In addition, the higher fatty acid constituting the aliphatic ester compound is preferably an aliphatic carboxylic acid having 10 to 32 carbon atoms, and specific examples thereof include saturated aliphatic carboxylic acids such as decanoic acid, undecanoic acid, dodecanoic acid, tridecanoic acid, tetradecanoic acid, pentadecanoic acid, hexadecanoic acid (palmitic acid), heptadecanoic acid, octadecanoic acid (stearic acid), nonadecanoic acid, icosanoic acid, docosanoic acid, and hexacosanoic acid, as well as unsaturated aliphatic carboxylic acids such as palmitoleic acid, oleic acid, linoleic acid, linolenic acid, eicosenoic acid, eicosapentaenoic acid, and cetoleic acid. Among these, the aliphatic carboxylic acid is more preferably one having 10 to 22 carbon atoms, and even more preferably one having 14 to 20 carbon atoms. Furthermore, saturated aliphatic carboxylic acids having 14 to 20 carbon atoms are preferred, and stearic acid and palmitic acid are particularly preferred. Aliphatic carboxylic acids such as stearic acid are often in the form of a mixture containing other carboxylic acid components having different numbers of carbon atoms. Among the above-mentioned saturated fatty acid esters, ester compounds obtained from stearic acid or palmitic acid, which are produced from such natural fats and oils and are in the form of a mixture containing other carboxylic acid components, are preferably used.

[0041] Specific examples of the ester compounds that are preferably used include those containing glycerin monostearate, glycerin tristearate, and pentaerythritol tetrastearate as main components.

[0042] <Content of specific components in aromatic polycarbonate resin composition> The chlorine atom content in the aromatic polycarbonate resin composition of the present invention is preferably 30 ppm or less, more preferably 10 ppm or less, even more preferably 5 ppm or less, and particularly preferably 3 ppm or less, relative to the aromatic polycarbonate resin composition. Most of the chlorine atoms are those that remain in the aromatic polycarbonate resin from the chlorine-based organic solvent used in the polymer polymerization process, and in addition, they are derived from carbon tetrachloride contained as an impurity in the raw material phosgene and traces of unreacted chloroformate groups remaining in the polymer chain. If the amount of remaining chlorine-based organic solvent increases, the amount of trace volatile components detected from the resin will increase due to the volatilization and decomposition products of the chlorine-based organic solvent itself. The chlorine atom content in the aromatic polycarbonate resin composition of the present invention is measured by the combustion chlorine method.

[0043] The trace volatile components to be reduced in the present invention include the residual organic solvent components used in the above-mentioned polymer polymerization process, decomposition products of the residual organic solvent, volatile components and decomposition products from an aliphatic ester compound used as a mold release agent, which is an additive blended during extrusion, volatile components and decomposition products from a phosphorus-based compound used as a stabilizer, and phenol compounds derived from aromatic polycarbonate resins, etc. Phenol compounds derived from aromatic polycarbonate resins include unreacted phenol compounds remaining during polymer polymerization of aromatic polycarbonate resins, and compounds generated by decomposition of aromatic polycarbonate resins during extrusion pelletization.

[0044] These phenol compounds are phenol compounds having 6 to 18 carbon atoms, and include monohydric phenol compounds for blocking ends used in the production of aromatic polycarbonate resins, dihydric phenols as raw materials, and phenol compounds constituting additives, etc. Phenol compounds having a carbon number of more than 18 have low volatility and therefore have little effect on the achievement of the present invention.

[0045] Specific examples of the phenol compound having 6 to 18 carbon atoms include the above-mentioned raw material dihydric phenol, particularly bisphenol A, and the above-mentioned monohydric phenols used as end terminators, such as phenol, p-tert-butylphenol, p-cumylphenol, and isooctylphenol.

[0046] In the aromatic polycarbonate resin composition of the present invention, it is important to suppress the amount of outgassing. Although it is also important to reduce the amount of solvent such as methylene chloride as described above, it is particularly important to reduce the amount of additives other than methylene chloride and volatile components such as phenol compounds, because the composition is suitable for use as a material for containers and covers used for storing or transporting various precision electronic materials.

[0047] As for the amount of outgas generated in the aromatic polycarbonate resin composition, the amount of methylene chloride generated is preferably 500 ppb or less, and more preferably 300 ppb or less.

[0048] In addition, the amount of outgassing in the aromatic polycarbonate resin composition, that of volatile components other than methylene chloride, is preferably 10 ppb or less, more preferably 7 ppb or less, and even more preferably 5 ppb or less.

[0049] In addition, outgassing analysis (methylene chloride component) in aromatic polycarbonate resin composition The amount of methylene chloride and other components generated is measured by using a HS / GC / MS system, which combines the headspace (HS) method and gas chromatography / mass spectrometry (GC / MS), to measure the amount of gas components (methylene chloride and other components) generated when the sample is heated at 150°C for 1 hour.

[0050] <Method for reducing trace amounts of volatile components in aromatic polycarbonate resin compositions> The method for reducing the amount of volatile gas emitted from a resin composition according to the present invention is to "add a minimum amount of a specific aliphatic ester compound as an additive" when melt-extruding an aromatic polycarbonate resin powder granule alone or when melt-extruding an aromatic polycarbonate resin powder granule containing an additive.

[0051] As a method for reducing the amount of trace volatile gases emitted from the aromatic polycarbonate resin composition, it is also effective to further reduce the amount of chlorinated organic solvents and phenol compounds having 6 to 18 carbon atoms remaining in the aromatic polycarbonate resin composition. For example, there can be mentioned a method for enhancing drying of the aromatic polycarbonate resin in the latter stage of the polymer polymerization process, a method for drying an aromatic polycarbonate resin having an increased surface area, a method for washing aromatic polycarbonate resin powder particles with a poor solvent, and a method for enhancing devolatilization when the aromatic polycarbonate resin powder particles are melt-extruded.

[0052] Specifically, an effective method for enhancing the drying of the aromatic polycarbonate resin is to increase the drying temperature. However, it is not preferable to set the temperature at or above the softening point of the aromatic polycarbonate resin, and drying is usually performed at 90 to 140° C. In addition, there are methods such as extending the drying time and increasing the stirring efficiency of the aromatic polycarbonate resin during drying.

[0053] To increase the surface area of ​​the aromatic polycarbonate resin, it is preferable to make the aromatic polycarbonate resin into a powder shape with a small particle size, and for this purpose, a method such as strengthening the crushing of the aromatic polycarbonate resin is used. In particular, since the particles are too hard to crush dry resins, it is preferable to crush the resin in a slurry state containing an organic solvent or water after granulation. It is also effective to make it into a porous powder, and for example, there is a method of granulating the resin by dropping an aromatic polycarbonate resin solution dissolved in a good solvent into a poor solvent set at a temperature considerably higher than the boiling point of the good solvent while stirring.

[0054] By adopting a method of washing an aromatic polycarbonate resin, particularly a resin powder, with a poor solvent, phenolic compounds in the aromatic polycarbonate resin are extracted into the poor solvent. Further, this method also has the effect of replacing such a poor solvent with a chlorinated organic solvent in the aromatic polycarbonate resin and reducing the chlorinated organic solvent. Examples of the poor solvent include acetone, methanol, heptane, etc., and among them, acetone is preferably used.

[0055] As a method for enhancing devolatilization when melt-extruding an aromatic polycarbonate resin powder, specifically, a method of increasing the devolatilization area in the melt extruder is used. Further, there are methods such as setting a low devolatilization pressure or using a devolatilization aid such as water.

[0056] As a method for reducing carbon tetrachloride in an aromatic polycarbonate resin composition, a method of reducing the introduction of carbon tetrachloride by reducing the carbon tetrachloride concentration in raw material phosgene, specifically, adsorption and removal of carbon tetrachloride by activated carbon or separation and removal of carbon tetrachloride from phosgene by distillation using the boiling point difference between phosgene and carbon tetrachloride, etc. are mentioned. Further, as a method of using methylene chloride with a low carbon tetrachloride content, when continuously recycling methylene chloride, there is a method of removing carbon tetrachloride contained in the recycled methylene chloride by an operation such as distillation for a part or all of the recycled methylene chloride.

[0057] As a method for reducing the chloroformate group in an aromatic polycarbonate resin, there are a method of facilitating the completion of polymerization such as using a catalyst during polymerization or taking a sufficient polymerization time, and a method of washing the aromatic polycarbonate resin with an aqueous alkali solution such as an aqueous NaOH solution.

[0058] <Components other than component B (aliphatic ester compound)> In the polycarbonate resin composition of the present invention, various additives, other resins, and fillers may be blended as long as the effects of the present invention are not impaired, but it is preferable not to use them or to use them as little as possible.

[0059] In the present invention, the total amount of additives to be blended, including component B and additives other than component B, is 0.01 to 0.15 parts by weight, preferably 0.01 to 0.13 parts by weight, more preferably 0.015 to 0.10 parts by weight, and even more preferably 0.02 to 0.08 parts by weight, relative to 100 parts by weight of the aromatic polycarbonate resin. If it is within the above range, the mold releasability during molding is good, heat resistance during molding is excellent, and trace amounts of volatile components detected in the aromatic polycarbonate resin composition are suppressed, which is preferable.

[0060] In consideration of the above points, additives that are used to improve the thermal stability, designability, etc. of the aromatic polycarbonate resin composition of the present invention are advantageously used. These additives will be specifically described below.

[0061] [Heat stabilizer] The heat stabilizer may be blended in a small amount to prevent deterioration of the resin and prevent a decrease in molecular weight or deterioration of color during molding of the aromatic polycarbonate resin, within a range that does not impair the object of the present invention, and is preferably 0.001 to 0.03 parts by weight, more preferably 0.001 to 0.02 parts by weight, even more preferably 0.001 to 0.01 parts by weight, and particularly preferably 0.001 to 0.005 parts by weight, relative to 100 parts by weight of the aromatic polycarbonate resin. Within such a range, trace volatile components resulting from the volatilization of the heat stabilizer and the volatilization of decomposition products or altered products of the heat stabilizer are suppressed, which is preferable.

[0062] The aromatic polycarbonate resin composition of the present invention may contain a phosphorus-based heat stabilizer as a heat stabilizer.

[0063] Specific examples of such phosphorus-based heat stabilizers include phosphorous acid (phosphite), phosphonite, phosphinite, phosphine, phosphoric acid (phosphate), phosphonate, phosphinate, phosphine oxide, etc., each having an aromatic group or an aliphatic group, and among these, phosphites, phosphonites, phosphines, phosphonates, and phosphates are preferably used. Specific examples of the phosphite compound include trimethyl phosphite, triethyl phosphite, tripropyl phosphite, triisopropyl phosphite, tributyl phosphite, triphenyl phosphite, tris(nonylphenyl)phosphite, tridecyl phosphite, trioctyl phosphite, trioctadecyl phosphite, didecyl monophenyl phosphite, dioctyl monophenyl phosphite, diisopropyl monophenyl phosphite, monobutyl diphenyl phosphite, monodecyl diphenyl phosphite, monooctyl diphenyl phosphite, 2,2-methylenebis(4,6-di-tert-butylphenyl)octyl phosphite, tris(diethylphenyl)phosphite, tris(di-isopropylphenyl)phosphite, phenyl) phosphite, tris(di-n-butylphenyl) phosphite, tris(2,4-di-tert-butylphenyl) phosphite, tris(2,6-di-tert-butylphenyl) phosphite, distearyl pentaerythritol diphosphite, bis(2,4-di-tert-butylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-methylphenyl) pentaerythritol diphosphite, bis(2,6-di-tert-butyl-4-ethylphenyl) pentaerythritol diphosphite, phenyl bisphenol A pentaerythritol diphosphite, bis(nonylphenyl) pentaerythritol diphosphite, dicyclohexyl pentaerythritol diphosphite, etc. Furthermore, as other phosphite compounds, those having a cyclic structure that reacts with dihydric phenols can also be used.For example, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2,4-di-tert-butylphenyl)phosphite, 2,2'-methylenebis(4,6-di-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-methylenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, 2,2'-ethylidenebis(4-methyl-6-tert-butylphenyl)(2-tert-butyl-4-methylphenyl)phosphite, and the like can be mentioned.

[0064] Examples of the phosphonite compounds include tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,4-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,4'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-4,3'-biphenylene diphosphonite, tetrakis(2,6-di-tert-butylphenyl)-3,3'-biphenylene diphosphonite, bis(2,4-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, bis Examples of the phosphonite include (2,4-di-tert-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-n-butylphenyl)-3-phenyl-phenylphosphonite, bis(2,6-di-tert-butylphenyl)-4-phenyl-phenylphosphonite, and bis(2,6-di-tert-butylphenyl)-3-phenyl-phenylphosphonite. Tetrakis(di-tert-butylphenyl)-biphenylene diphosphonite and bis(di-tert-butylphenyl)-phenyl-phenylphosphonite are preferred, and tetrakis(2,4-di-tert-butylphenyl)-biphenylene diphosphonite and bis(2,4-di-tert-butylphenyl)-phenyl-phenylphosphonite are more preferred. Such phosphonite compounds can be used in combination with the phosphite compounds having an aryl group substituted with two or more alkyl groups, and are therefore preferred.

[0065] Examples of the phosphine compound include triethylphosphine, tripropylphosphine, tributylphosphine, trioctylphosphine, triamylphosphine, dimethylphenylphosphine, dibutylphenylphosphine, diphenylmethylphosphine, diphenyloctylphosphine, triphenylphosphine, tri-p-tolylphosphine, trinaphthylphosphine, and diphenylbenzylphosphine. A particularly preferred phosphine compound is triphenylphosphine.

[0066] Examples of the phosphonate compound include dimethyl benzenephosphonate, diethyl benzenephosphonate, and dipropyl benzenephosphonate.

[0067] Examples of the phosphate compound include tributyl phosphate, trimethyl phosphate, tricresyl phosphate, triphenyl phosphate, trichlorophenyl phosphate, triethyl phosphate, diphenyl cresyl phosphate, diphenyl monoorthoxenyl phosphate, tributoxyethyl phosphate, dibutyl phosphate, dioctyl phosphate, diisopropyl phosphate, and the like, and preferably triphenyl phosphate and trimethyl phosphate. Among these, tris(2,4-di-tert-butylphenyl)phosphite, tetrakis(2,4-di-tert-butylphenyl)-4,4'-biphenylenediphosphona bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, bis(2,4-di-cumylphenyl)pentaerythritol diphosphite are preferred; bis(2,6-di-tert-butyl-4-methylphenyl)pentaerythritol diphosphite, tris(2,4-di-tert-butylphenyl)phosphite are more preferred; tris(2,4-di-tert-butylphenyl)phosphite is particularly preferred.

[0068] [Hindered phenol-based antioxidants] The aromatic polycarbonate resin composition of the present invention can be blended with a hindered phenol-based antioxidant within a range that does not impair the object of the present invention. The polycarbonate resin composition of the present disclosure has dry heat resistance such as little deterioration in color during molding processing or little discoloration of molded products during long-term use at high temperatures, but when further high dry heat resistance is to be imparted, blending of such an antioxidant is effective.

[0069] Examples of the hindered phenol stabilizer include n-octadecyl-β-(4'-hydroxy-3',5'-di-tert-butylphenyl)propionate, 2,6-di-tert-butyl-4-(N,N-dimethylaminomethyl)phenol, 3,5-di-tert-butyl-4-hydroxybenzylphosphonate diethyl ester, 2,2'-methylenebis(4-methyl-6-tert-butylphenol), 2,2'-methylenebis(4-ethyl-6-tert-butylphenol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-cyclohexylphenol), 1,6-hexanediol bis[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], bis[2 -tert-butyl-4-methyl 6-(3-tert-butyl-5-methyl-2-hydroxybenzyl)phenyl] terephthalate, 4,4'-thiobis(3-methyl-6-tert-butylphenol), 2,2'-thiobis(4-methyl-6-tert-butylphenol), bis(3,5-di-tert-butyl-4-hydroxybenzyl)sulfide, 4,4'-di-thiobis(2,6-di-tert-butylphenol), 4,4'-tri-thiobis(2,6-di-tert-butylphenol), 2,2-thiodiethylene bis-[3-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate], and tetrakis[methylene-3-(3',5'-di-tert-butyl-4-hydroxyphenyl)propionate]methane. All of these are commercially available. The above hindered phenol-based stabilizers can be used alone or in combination of two or more kinds.

[0070] [Bluing agent] In order to eliminate the yellowish color of the molded product, the aromatic polycarbonate resin composition of the present invention can be blended with a bluing agent within a range that does not impair the object of the present invention. There is no particular restriction on the bluing agent as long as it is used for polycarbonate resins. In general, anthraquinone dyes are preferred because they are easily available.

[0071] Specific examples of the bluing agent include Solvent Violet 13 (CA. No. (Color Index No.) 60725; Trade name: Bayer "Macrolex Violet B", Mitsubishi Chemical "Diaresin Blue G", Sumitomo Chemical "Sumiplast Violet B"); Solvent Violet 31 (CA. No. 68210; Trade name: Mitsubishi Chemical "Diaresin Violet D"); Solvent Violet 33 (CA. No. 60725; Trade name: Mitsubishi Chemical "Diaresin Blue J"); Solvent Blue 94 (CA. No. 61500; Trade name: Mitsubishi Chemical "Diaresin Blue N"); Solvent Violet 36 (CA. No. 68210; Trade name: Bayer "Macrolex Violet 3R"); Representative examples include Blue 97 (trade name "Macrolex Blue RR" manufactured by Bayer) and the general name Solvent Blue 45 (CA. No. 61110; trade name "Polysynthren Blue RLS" manufactured by Clariant). Taking into consideration the visual transmittance and the like, the bluing agent can be contained in the aromatic polycarbonate resin usually at a concentration of 0.3 to 1.2 ppm.

[0072] [Fluorescent whitening agents] In the aromatic polycarbonate resin composition of the present invention, the fluorescent brightener can be used within a range that does not impair the object of the present invention, so long as it is used to improve the color tone of the resin, etc. to white or bluish white. Examples of the fluorescent brightener include stilbene-based, benzimidazole-based, benzoxazole-based, naphthalimide-based, rhodamine-based, coumarin-based, and oxazine-based compounds. Specific examples include CI Fluorescent Brightener 219:1, Eastman Chemical Company's EASTOBRITE OB-1, and Hakkol Chemical Company's "Hakkol PSR." The fluorescent brightener absorbs ultraviolet energy of light and emits this energy in the visible range.

[0073] [Other heat stabilizers] Other heat stabilizers that may be blended in the aromatic polycarbonate resin composition of the present invention include, for example, sulfur-based heat stabilizers. Examples of sulfur-based heat stabilizers include pentaerythritol-tetrakis (3-laurylthiopropionate), pentaerythritol-tetrakis (3-myristylthiopropionate), pentaerythritol-tetrakis (3-stearylthiopropionate), dilauryl-3,3'-thiodipropionate, dimyristyl-3,3'-thiodipropionate, and distearyl-3,3'-thiodipropionate. Among these, pentaerythritol-tetrakis (3-laurylthiopropionate), pentaerythritol-tetrakis (3-myristylthiopropionate), dilauryl-3,3'-thiodipropionate, and dimyristyl-3,3'-thiodipropionate are preferred. Particularly preferred is pentaerythritol-tetrakis(3-laurylthiopropionate). The thioether compound is commercially available from Sumitomo Chemical Co., Ltd. under the trade names Sumilizer TP-D (trade name) and Sumilizer TPM (trade name), and is therefore easily available.

[0074] [Other resins and elastomers] The aromatic polycarbonate resin composition of the present invention may contain other resins or elastomers in an amount that does not impair the object of the present invention, that is, in an extremely small amount.

[0075] Examples of such other resins include polyester resins such as polyethylene terephthalate and polybutylene terephthalate, polyamide resins, polyimide resins, polyetherimide resins, polyurethane resins, polyphenylene ether resins, polyphenylene sulfide resins, polysulfone resins, polyolefin resins such as polyethylene and polypropylene, polystyrene resins, acrylonitrile / styrene copolymers (AS resins), acrylonitrile / butadiene / styrene copolymers (ABS resins), polymethacrylate resins, phenolic resins, and epoxy resins.

[0076] Examples of elastomers include isobutylene / isoprene rubber, styrene / butadiene rubber, ethylene / propylene rubber, acrylic elastomers, silicone rubber, polyester elastomers, polyamide elastomers, and core-shell elastomers such as MBS (methyl methacrylate / styrene / butadiene) rubber and MAS (methyl methacrylate / acrylonitrile / styrene) rubber.

[0077] [Ingredients other than those mentioned above] In addition to the above, known additives may be blended into the resin composition of the present invention in order to impart various functions to the molded article or to improve the properties thereof, so long as the object of the present invention is not impaired.

[0078] <Production of polycarbonate resin composition> Any method can be used to produce the polycarbonate resin composition of the present invention. For example, the A component, the B component, and any other components can be thoroughly mixed using a premixing means such as a V-type blender, a Henschel mixer, a mechanochemical device, or an extrusion mixer, and then granulated using an extrusion granulator or a briquetting machine, if necessary, and then melt-kneaded using a melt kneader, such as a vented twin-screw extruder, and pelletized using a pelletizer or other device. As an alternative method, the A component, the B component, and any other components can be independently supplied to a melt kneader, such as a vented twin-screw extruder, a method in which the A component and a part of the other components are premixed and then supplied to the melt kneader independently of the remaining components, a method in which the B component is diluted and mixed with water or an organic solvent and then supplied to the melt kneader, or such a diluted mixture is premixed with the other components and then supplied to the melt kneader. If any of the components to be blended is liquid, a so-called liquid injection device or liquid addition device can be used to supply the components to the melt kneading extruder. It is also possible to use a device for injecting water as a devolatilizing aid into the melt kneading extruder.

[0079] <Molded products> The aromatic polycarbonate resin composition can be molded into a molded article by a commonly known method such as injection molding, extrusion molding, compression molding, etc., either as it is or after being pelletized in a melt extruder as described above.

[0080] Examples of the molded products include molded products used for various industrial applications such as in the field of office automation equipment and the field of electrical and electronic equipment. Specific examples include molded products as exterior molded products or peripheral molded members that cover electronic components, electronic substrates, magnetic disks, semiconductor wafers such as wafers processed into integrated circuit chips, precision substrates such as mask glasses, and other precision electronic materials, molded products as containers for storing, transporting, conveying, and storing the various electronic materials described above, and molded products as molded members that constitute containers. Among these, thin plate storage and transport containers used for storing or transporting various precision electronic materials such as magnetic disks or wafers processed into integrated circuit chips are preferred, and storage and transport containers for semiconductor wafers are particularly preferred. EXAMPLES

[0081] The present invention will be described in detail below with reference to examples, but is not limited thereto. The aromatic polycarbonate resin powder obtained in each example, the characteristic values ​​of the aliphatic ester compound used in each example, and the polycarbonate resin composition pellet obtained by melt extrusion were evaluated according to the following methods (1) to (5).

[0082] (1) Acid value The acid value (KOHmg / g) was determined by neutralization titration method in accordance with JIS K 0070.

[0083] (2) 5% weight loss temperature by TGA (thermogravimetric analysis) Using a Discovery SDT 650 manufactured by TA-instruments, the temperature was raised at 20°C / min in a N2 atmosphere, and the temperature at which the weight loss of the sample reached 5% of the charged weight was measured as the 5% weight loss temperature in TGA (thermogravimetric analysis).

[0084] (3) Viscosity average molecular weight 0.7 g of aromatic polycarbonate resin powder was dissolved in 100 ml of methylene chloride, and the specific viscosity of the resulting solution was measured at 20°C using an Ostwald viscometer. The viscosity average molecular weight (M) of the carbonate resin was determined. Specific viscosity (η SP )=(t-t0) / t0 [t0 is the number of seconds that methylene chloride falls, and t is the number of seconds that the sample solution falls] η SP / c=[η]+0.45×[η] 2 c (where [η] is the intrinsic viscosity) [η]=1.23×10 -4 M 0.83 c=0.7

[0085] (4) Chlorine atom content Measurements were performed by the combustion chlorine method using a chlorine sulfur analyzer TOX-2100H manufactured by Nitto Seiko Analytech Co., Ltd. (formerly Mitsubishi Chemical Analytech). Specifically, the sample (pellet) was heated in an electric furnace (920°C) to completely vaporize it, and the vaporized gas was passed through sulfuric acid to dehydrate it, after which it was adsorbed into a chlorine electrolyte (sodium acetate). The potential difference generated by the adsorption was returned to the original potential by potentiometric titration. The chlorine atom content was calculated from the energy required to return the potential to the original value.

[0086] (5) Outgassing analysis The gas components (methylene chloride and other components) generated when 3 g of a sample (pellet) was heated at 150 for 1 hour were measured using an HS / GC / MS system that combines headspace (HS) method and gas chromatography / mass spectrometry (GC / MS) using an Agilent Technologies 6890NGC & 5975B GC / MSD.

[0087] (6) Molding retention test In order to evaluate the molding retention stability, a molding retention test equivalent to a molding heat resistance test was carried out. The pellets obtained in each example were dried in a hot air dryer at 120°C for 5 hours, and a three-stage plate with a width of 50 mm, a length of 90 mm, and a thickness of 3 mm (length 20 mm), 2 mm (length 45 mm), and 1 mm (length 25 mm) from the gate side was molded using an injection molding machine J180ADS manufactured by Japan Steel Works, Ltd., at a cylinder temperature of 350°C, a mold temperature of 80°C, and a 1-minute cycle. After 20 consecutive shots of molding, the resin was retained in the cylinder of the injection molding machine at a cylinder temperature of 350°C for 10 minutes, and the hue (L) in the CIE color system was measured for the 2 mm-thick part of the test piece before and after retention, according to JIS K-7105 and JIS Z 8781-4, using a Color-Eye7000A manufactured by X-Rite (formerly Gretag Macbeth) under the conditions of a light source D65, a viewing angle of 10 degrees, and a transmission method. * , a * , b * ) and calculate the color difference ΔE according to the following formula (a) * ΔE was calculated. * The smaller the value, the more excellent the molding retention stability. ΔE * = {(ΔL * ) 2 +(Δa * ) 2 +(Δb * ) 2} 1 / 2 ...Formula (a) Color of "Formed plate before retention": L * , a * , b * Color of "Formed plate after retention": L * ',a * ',b * ' ΔL * :L * -L * ' Δa * :a * -a * ' Δb * :b * -b * '

[0088] (7) Demolding load The pellets were dried at 120°C for 5 hours, and then injection molded using an injection molding machine (Japan Steel Works, Ltd.: J180ADS) with a cylinder temperature of 320°C and a mold temperature of 90°C using a cup-shaped mold for evaluating mold releasability (opening outer diameter: 70 mm, bottom outer diameter: 63 mm, height: 20 mm, thickness: 4 mm), and the ejection load at the time of mold release was measured using a load cell. The smaller this value, the better the mold releasability.

[0089] [Example 1] A reactor equipped with a thermometer, stirrer, and reflux condenser was charged with 2,194 parts of ion-exchanged water and 402 parts of 48% aqueous sodium hydroxide solution, and 2,2-bis(4-hydroxyphenyl)propane was added. After dissolving 575 parts of bread and 1.2 parts of hydrosulfite, 1810 parts of methylene chloride was added, and 283 parts of phosgene treated with activated carbon was blown in at 15 to 25°C for 40 minutes under stirring. After the end of the phosgene blowing, 72 parts of 48% aqueous sodium hydroxide solution and 18.5 parts of p-tert-butylphenol were added, emulsified by stirring, and after 10 minutes, treated with a homomixer, and left unstirred at a temperature range of 30 to 33°C for 3 hours to complete the reaction. After the reaction was completed, 1810 parts of methylene chloride was added, stirred and mixed for 20 minutes, and then allowed to stand to separate the polycarbonate resin organic solvent solution phase and the aqueous phase. To 1 part of the separated polycarbonate resin organic solvent solution, 1 part of ion-exchanged water was added to wash and separate three times until the conductivity of the aqueous phase was almost the same as that of the ion-exchanged water. The washed polycarbonate resin organic solvent solution was filtered through a SUS304 filter with a nominal filtration accuracy of 1 μm.

[0090] Next, the obtained polycarbonate resin organic solvent solution was poured into a kneader charged with 45°C hot water (an amount occupying about 10% of the kneader's internal space volume) over a period of 1 hour while stirring, and methylene chloride was evaporated and removed at an internal temperature of 45°C while blowing in steam to obtain a mixture of polycarbonate powder particles and water. The mixture of powder particles and water was passed through a grinder to be pulverized, and then poured into a hot water treatment tank equipped with an agitator whose water temperature was controlled at 95°C, where water was added to a mixture ratio of 25 parts powder particles and 75 parts water, and mixed with the agitator for 30 minutes. The mixture of powder particles and water was separated with a centrifuge to obtain a powder particle containing 3.5% by weight of methylene chloride and 10% by weight of water. Next, this powder was continuously fed at 50 kg / Hr (polycarbonate resin equivalent) to a SUS316L conductive heat-receiving grooved two-axis agitator continuous dryer controlled at 140°C, and dried for an average drying time of 8 hours to obtain a powder with a viscosity average molecular weight of 18,500.

[0091] Next, 0.015 parts by weight of Unistar H-476-S (trade name) (main component: pentaerythritol tetrastearate [acid value: 3.1, TGA 5% weight loss temperature: 378 ° C.] manufactured by NOF Corp. was added to the obtained polycarbonate powder particles and stirred and mixed for 20 minutes using a Nauta mixer. The mixture was fed from the raw material feed port at 30 kg / Hr using a twin-screw extruder (manufactured by Japan Steel Works, Ltd.: TEX30α) having two vents and an ion-exchanged water inlet between the vents and a 20 μm disk-type screen between the cylinder and the die, and melt-extruded into strands under extrusion conditions of a screw rotation speed of 300 rpm, a resin temperature of 280 ° C., and a vent vacuum of 1 kPa. The melt-extruded strands were cooled in a cooling bath and then cut with a cutter to obtain pellets with a diameter of 3 mm and a length of 3 mm. In addition, 0.5 parts by weight of ion-exchanged water was supplied as a devolatilizing aid from the ion-exchanged water inlet based on 100 parts by weight of the polycarbonate resin composition. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 1.

[0092] [Example 2] A reactor equipped with a thermometer, a stirrer and a reflux condenser was charged with 2194 parts of ion-exchanged water and 402 parts of 48% aqueous sodium hydroxide solution, and 575 parts of 2,2-bis(4-hydroxyphenyl)propane and 1.2 parts of hydrosulfite were dissolved therein, and then 1810 parts of methylene chloride was added, and 283 parts of activated carbon-treated phosgene was blown in at 15-25°C for 40 minutes while stirring. After the end of the phosgene blowing, 72 parts of 48% aqueous sodium hydroxide solution and 18.5 parts of p-tert-butylphenol were added, emulsified by stirring, and treated with a homomixer after 10 minutes, and then left unstirred at a temperature range of 30-33°C for 3 hours to complete the reaction. After the end of the reaction, 1810 parts of methylene chloride was added, and the mixture was stirred and mixed for 20 minutes, and then allowed to stand, and the organic solvent solution phase of the polycarbonate resin and the aqueous phase were separated. Washing and separation were repeated three times by adding 1 part of ion-exchanged water to 1 part of the organic solvent solution of the separated polycarbonate resin until the conductivity of the aqueous phase was almost the same as that of the ion-exchanged water. The washed organic solvent solution of the polycarbonate resin was filtered through a SUS304 filter with a nominal filtration accuracy of 1 μm, and then tris(2,4-di-tert-butylphenyl)phosphite was added in an amount of 0.0025 parts by weight per 100 parts by weight of the polycarbonate resin.

[0093] Next, the obtained polycarbonate resin organic solvent solution was poured into a kneader charged with 45°C hot water (an amount occupying about 10% of the kneader's internal space volume) over a period of 1 hour while stirring, and methylene chloride was evaporated and removed at an internal temperature of 45°C while blowing in steam to obtain a mixture of polycarbonate powder particles and water. The mixture of powder particles and water was passed through a grinder to be pulverized, and then poured into a hot water treatment tank equipped with an agitator whose water temperature was controlled at 95°C, where water was added to a mixture ratio of 25 parts powder particles and 75 parts water, and mixed with the agitator for 30 minutes. The mixture of powder particles and water was separated with a centrifuge to obtain a powder particle containing 3.5% by weight of methylene chloride and 10% by weight of water. Next, this powder was continuously fed at 50 kg / Hr (polycarbonate resin equivalent) to a SUS316L conductive heat-receiving grooved two-axis agitator continuous dryer controlled at 140°C, and dried for an average drying time of 8 hours to obtain polycarbonate resin powder with a viscosity average molecular weight of 18,500.

[0094] Next, 0.03 parts by weight of Unistar H-476-S (trade name) (main component: pentaerythritol tetrastearate) manufactured by NOF Corp. was added to the obtained polycarbonate powder particles with respect to 100 parts by weight of polycarbonate resin, and the mixture was stirred and mixed for 20 minutes using a Nauta mixer. The mixture was fed from the raw material feed port of a twin-screw extruder (TEX30α manufactured by Japan Steel Works, Ltd.) having two vents and an ion-exchanged water inlet between the vents, and a 20 μm disk-type screen was attached between the cylinder and the die, at 30 kg / Hr, and strands were melt-extruded under extrusion conditions of a screw rotation speed of 300 rpm, a resin temperature of 280° C., and a vent vacuum of 1 kPa. The melt-extruded strands were cooled in a cooling bath, and then cut with a cutter to obtain pellets with a diameter of 3 mm and a length of 3 mm. Incidentally, 0.5 parts by weight of ion-exchanged water was fed from the ion-exchanged water inlet as a devolatilizing aid with respect to 100 parts by weight of the polycarbonate resin composition. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above. The results are shown in Table 1.

[0095] [Example 3] The same procedure was carried out as in Example 2, except that the amount of p-tert-butylphenol added was changed to 14.9 parts, to obtain polycarbonate resin powder and pellets having a viscosity average molecular weight of 22,000. The obtained pellets were subjected to the measurements and evaluations of (4) to (7) above, and the results are shown in Table 1.

[0096] [Example 4] A reactor equipped with a thermometer, a stirrer and a reflux condenser was charged with 2194 parts of ion-exchanged water and 402 parts of 48% aqueous sodium hydroxide solution, and 575 parts of 2,2-bis(4-hydroxyphenyl)propane and 1.2 parts of hydrosulfite were dissolved therein, and then 1810 parts of methylene chloride was added, and 283 parts of activated carbon-treated phosgene was blown in at 15-25°C for 40 minutes while stirring. After the end of the phosgene blowing, 72 parts of 48% aqueous sodium hydroxide solution and 18.5 parts of p-tert-butylphenol were added, emulsified by stirring, and treated with a homomixer after 10 minutes, and then left unstirred at a temperature range of 30-33°C for 3 hours to complete the reaction. After the end of the reaction, 1810 parts of methylene chloride was added, and the mixture was stirred and mixed for 20 minutes, and then allowed to stand, and the organic solvent solution phase of the polycarbonate resin and the aqueous phase were separated. One part of ion-exchanged water was added to one part of the organic solvent solution of the separated polycarbonate resin, and washing and separation were repeated three times until the conductivity of the aqueous phase became almost the same as that of the ion-exchanged water. The washed organic solvent solution of the polycarbonate resin was filtered through a SUS304 filter with a nominal filtration accuracy of 1 μm, and then 4,4'-biphenylenediphosphinic acid tetrakis(2,4-di-tert-butylphenyl) was added in an amount of 0.0025 parts by weight per 100 parts by weight of the polycarbonate resin.

[0097] Next, the obtained polycarbonate resin organic solvent solution was poured into a kneader charged with 45°C hot water (an amount occupying about 10% of the kneader's internal space volume) over a period of 1 hour while stirring. While blowing in steam, methylene chloride was evaporated and removed at an internal temperature of 45°C to obtain a mixture of polycarbonate powder and water. The mixture of powder and water was passed through a grinder to grind it, and then charged into a hot water treatment tank equipped with an agitator whose water temperature was controlled at 95°C. Water was added to the mixture to give a mixing ratio of 25 parts powder and 75 parts water, and the mixture was mixed with the agitator for 30 minutes. The mixture of powder and water was separated with a centrifuge to obtain a powder containing 3.5% by weight of methylene chloride and 10% by weight of water. Next, the powder was continuously fed at 50 kg / Hr (polycarbonate resin equivalent) to a SUS316L conductive heat receiving groove type two-shaft agitator continuous dryer controlled at 140°C, and dried under the condition of an average drying time of 8 hours to obtain a polycarbonate resin powder having a viscosity average molecular weight of 18,500.

[0098] Next, 0.045 parts by weight of Unistar H-476-S (trade name) (main component: pentaerythritol tetrastearate) manufactured by NOF Corp. was added to the obtained polycarbonate powder particles with respect to 100 parts by weight of polycarbonate resin, and the mixture was stirred and mixed for 20 minutes using a Nauta mixer. The mixture was fed from the raw material feed port of a twin-screw extruder (TEX30α manufactured by Japan Steel Works, Ltd.) having two vents and an ion-exchanged water inlet between the vents, and a 20 μm disk-type screen was attached between the cylinder and the die, at 30 kg / Hr, and strands were melt-extruded under extrusion conditions of a screw rotation speed of 300 rpm, a resin temperature of 280° C., and a vent vacuum of 1 kPa. The melt-extruded strands were cooled in a cooling bath, and then cut with a cutter to obtain pellets with a diameter of 3 mm and a length of 3 mm. Incidentally, 0.5 parts by weight of ion-exchanged water was fed from the ion-exchanged water inlet as a devolatilizing aid with respect to 100 parts by weight of the polycarbonate resin composition. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above. The results are shown in Table 1.

[0099] [Example 5] The same procedure as in Example 1 was carried out, except that the amount of Unistar H-476-S (trade name) manufactured by NOF Corporation added was changed to 0.1 parts by weight.

[0100] [Example 6] The same procedure was carried out as in Example 2, except that 0.015 parts by weight of Roxiol VPG861 (product name) (main component: pentaerythritol tetrastearate [acid value: 1.0, TGA 5% weight loss temperature: 382°C]) manufactured by Emery Oleochemicals Japan Co., Ltd. was added to 100 parts by weight of polycarbonate resin instead of 0.03 parts by weight of Unistar H-476-S (product name) manufactured by NOF Corp., based on 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 1.

[0101] [Example 7] The same procedure was carried out as in Example 1, except that 0.03 parts by weight of Roxiol VPG861 (product name) manufactured by Emery Oleochemicals Japan Ltd. was added to 100 parts by weight of polycarbonate resin instead of 0.015 parts by weight of Unistar H-476-S (product name) manufactured by NOF Corp., per 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 1.

[0102] [Example 8] The same procedure was carried out as in Example 1, except that 0.045 parts by weight of Roxiol VPG861 (product name) manufactured by Emery Oleochemicals Japan Ltd. was added to 100 parts by weight of polycarbonate resin instead of 0.015 parts by weight of Unistar H-476-S (product name) manufactured by NOF Corp. was added to 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 1.

[0103] [Example 9] The same procedure was carried out as in Example 1, except that 0.1 part by weight of Roxiol VPG861 (product name) manufactured by Emery Oleochemicals Japan Ltd. was added to 100 parts by weight of polycarbonate resin instead of 0.015 part by weight of Unistar H-476-S (product name) manufactured by NOF Corp. was added to 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 1.

[0104] [Example 10] The same procedure was carried out as in Example 1, except that, instead of adding 0.015 parts by weight of Unistar H-476-S (trade name) manufactured by NOF Corp. to 100 parts by weight of polycarbonate resin, the amount of Unistar H-476-S (trade name) manufactured by NOF Corp. was changed to 0.04 parts by weight, and 0.01 parts by weight of Rikestar EW400 (trade name) manufactured by Riken Vitamin Co., Ltd. (main component: pentaerythritol tetrastearate [acid value: 10, TGA 5% weight loss temperature: 322°C]) was added. The obtained pellets were subjected to the measurements and evaluations of (4) to (7) above, and the results are shown in Table 1.

[0105] [Example 11] The same procedure was carried out as in Example 1, except that, instead of adding 0.015 parts by weight of Unistar H-476-S (trade name) manufactured by NOF Corp. to 100 parts by weight of polycarbonate resin, the amount of Unistar H-476-S (trade name) manufactured by NOF Corp. was changed to 0.01 parts by weight, and 0.04 parts by weight of Rikemal S-100A (trade name) manufactured by Riken Vitamin Co., Ltd. (main component: glycerin monostearate [acid value: 2.0, TGA 5% weight loss temperature: 290°C]) was added. The obtained pellets were subjected to the measurements and evaluations of (4) to (7) above, and the results are shown in Table 1.

[0106] [Example 12] The same procedure was carried out as in Example 3, except that ion-exchanged water (devolatilizing aid) was not supplied during melt extrusion. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 1.

[0107] [Example 13] The same procedure was carried out as in Example 5, except that ion-exchanged water (devolatilizing aid) was not supplied during melt extrusion. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 1.

[0108] [Example 14] The same procedure was carried out as in Example 4, except that an aromatic polycarbonate resin powder (Teijin Ltd.: Panlite (trademark) L-1225WX) having a viscosity average molecular weight of 19,700 obtained by polymerizing bisphenol A and phosgene by an interfacial polymerization method was used instead of the polycarbonate resin powder having a viscosity average molecular weight of 18,500 obtained in Example 4. The obtained pellets were subjected to the measurements and evaluations of (4) to (7) above, and the results are shown in Table 1.

[0109] [Comparative Example 1] The same procedure was carried out as in Example 5, except that the amount of Unistar H-476-S (product name) manufactured by NOF Corp. added was changed to 0.15 parts by weight. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 2.

[0110] [Comparative Example 2] In Example 12, 0.03 parts by weight of Unistar H-476-S (trade name) manufactured by NOF Corp. was added per 100 parts by weight of polycarbonate resin, and Riken Vitamin Co., Ltd. The same procedure was carried out, except that 0.03 parts by weight of Rikemal S-100A (trade name) manufactured by Epson Corporation was added per 100 parts by weight of the polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 2.

[0111] [Comparative Example 3] The same procedure was carried out as in Example 13, except that 0.1 parts by weight of Rikemal S-100A (trade name) manufactured by Riken Vitamin Co., Ltd. was added to 100 parts by weight of polycarbonate resin instead of 0.1 parts by weight of Unistar H-476-S (trade name) manufactured by NOF Corp., per 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 2.

[0112] [Comparative Example 4] The same procedure was carried out as in Example 13, except that 0.03 parts by weight of Rikestar EW400 (product name) (main component: pentaerythritol tetrastearate [acid value: 10, TGA 5% weight loss temperature: 322°C]) manufactured by Riken Vitamin Co., Ltd. was added to 100 parts by weight of polycarbonate resin instead of 0.1 parts by weight of Unistar H-476-S (product name) manufactured by NOF Corp., based on 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 2.

[0113] [Comparative Example 5] The same procedure was carried out as in Example 5, except that 0.03 parts by weight of Rikestar EW400 (product name) manufactured by Riken Vitamin Co., Ltd. was added to 100 parts by weight of polycarbonate resin instead of 0.1 parts by weight of Unistar H-476-S (product name) manufactured by NOF Corp., per 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 2.

[0114] [Comparative Example 6] The same procedure was carried out as in Example 13, except that 0.1 parts by weight of Likester EW400 (product name) manufactured by Riken Vitamin Co., Ltd. was added per 100 parts by weight of polycarbonate resin instead of 0.1 parts by weight of Unistar H-476-S (product name) manufactured by NOF Corp. per 100 parts by weight of polycarbonate resin. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 2.

[0115] [Comparative Example 7] The same procedure was carried out as in Example 5, except that the amount of Unistar H-476-S (product name) manufactured by NOF Corp. added was changed to 0.005 parts by weight. The obtained pellets were subjected to the measurements and evaluations (4) to (7) above, and the results are shown in Table 2.

[0116] [Table 1]

[0117] [Table 2] [Industrial Applicability]

[0118] The polycarbonate resin composition of the present invention has excellent mold releasability and molding heat resistance, and further has a significantly reduced amount of volatile gases. Transparent molded articles obtained from the polycarbonate resin composition are useful for various industrial applications such as in the fields of office automation equipment and electrical and electronic equipment, and are particularly useful as containers for storing and transporting thin plates such as semiconductor wafers.

Claims

1. (B) 0.01 to 0.12 parts by weight of a full ester of pentaerythritol (component B) is blended with 100 parts by weight of an aromatic polycarbonate resin (component A), the total amount of blended additives including component B and additives other than component B is 0.01 to 0.15 parts by weight, and the viscosity average molecular weight of component A is in the range of 18,000 to 23,000, The component B is (i) the acid value is 5 or less; (ii) the 5% weight loss temperature by TGA (thermogravimetric analysis) is 300° C. or higher; A thin plate storage and transport container molded from an aromatic polycarbonate resin composition.

2. 2. The thin plate storage and transport container according to claim 1, wherein the B component is blended in an amount of 0.015 to 0.07 parts by weight, and the total amount of blended additives including the B component and additives other than the B component is 0.015 to 0.10 parts by weight.

3. 3. The thin plate storage and transport container according to claim 1, wherein the component B has a 5% weight loss temperature of 330[deg.] C. or higher by TGA (thermogravimetric analysis).

4. 4. The thin plate storage and transportation container according to claim 1, wherein the aromatic polycarbonate resin composition has a chlorine atom content of 5 ppm or less.

5. 5. The thin plate storing and transporting container according to claim 4, which is a container for storing and transporting semiconductor wafers.

Citation Information

Patent Citations

  • Rotary electric machine

    JP1982049335A

  • Power distribution board

    JP1983006008A

  • Iron-chromium-aluminum alloy

    JP1983093856A

  • Preparation of polycarbonate pellet

    JP1998292050A

  • Production of polycarbonate pellet

    JP1998298301A